Type material of Carlos L. Spegazzini in the Museo de La Plata Herbarium (LP), Argentina : III. Cactaceae - Katinas, Liliana (2004)
A catalogue of the Cactaceae type material of Carlos Luis Spegazzini (1858-1926) deposited in the Herbarium of Museo de La Plata (LP), Argentina, is presented. Spegazzini´s collection of vascular plant types includes ca. 700 specimens. This analysis revealed 93 type specimens and photographs of the specimens of the family Cactaceae, 70 of which are deposited in LP. This article includes a list of original names arranged alphabetically, the current names with authors, the original citation or protologue, the exsiccatae followed by the type category, the photographs of the specimens taken by Spegazzini, and all significant observations. In addition, some photographs of living specimens taken by Spegazzini and a list of specimens not found in LP were also included.